Pemetaan Kesesuaian Pemanfaatan Lahan Perkebunan Kelapa Sawit di Kabupaten Dharmasraya - Fauzil Azim; Dwi Arini; Fajrin Fajrin; Defwaldi Defwaldi; Dwi Marsiska Driptufany (Politeknik Kampar, 2025)
The majority of Indonesians work as farmers, and oil palm plantations have become one of the key pillars in Indonesia's economy. This commodity contributes significantly to the country's foreign exchange, employment opportunities, and economic growth across various regions, particularly in Sumatra. Dharmasraya Regency, located in West Sumatra, is one of the areas with a substantial area of oil palm plantations. Therefore, it is essential to conduct a detailed land suitability mapping to ensure that the development is carried out sustainably and does not harm the environment. In this study, the overlay method was applied, considering several parameters such as slope, surface temperature, rainfall, soil texture, and elevation. The results of this study produced a land suitability map for oil palm plantations, which indicates the suitability levels of the land. (S1) Highly Suitable with an area of 57,107.17 ha, (S2) Suitable with an area of 53,217.43 ha, (S3) Less Suitable with an area of 167,281.13 ha, and (N) Not Suitable with an area of 25,211.35 ha.